Water quality and anthropogenic impact in the watersheds of service reservoirs in the Brazilian semi-arid region - Chaves, Luiz Carlos; Lopes, Fernando; Maia, Anthony Rafael; Meireles, Ana Célia; de Andrade, Eunice (Revista Ciência Agronômica, 2019)
The semi-arid region of Brazil is characterised by the irregular temporal and spatial distribution of the rainfall, which together with anthropogenic action causes degradation of the water quality. The aim of this study was to evaluate water quality in surface reservoirs in the Brazilian semi-arid region due to rainfall variability and the degree of anthropisation of the watersheds. Water samples were collected at the Orós, Trussu and Muquém reservoirs during August and December of 2012, April, October and December of 2013, and March and June of 2014 (dry and rainy periods). The following limnological attributes were analysed: electrical conductivity, pH, turbidity, transparency and chlorophyll-a, with the results evaluated using box plots, and the mean values compared by Student’s t-test. Anthropogenic data from the watersheds contributing to the reservoirs were used to correlate limnological attributes with the condition of the watersheds during the dry period of 2013. The rainfall was not sufficient to significantly improve the water quality of the reservoirs, and in the Orós Reservoir high levels of chlorophyll-a and turbidity occurred during both periods. Anthropisation of these areas has a direct influence on the water quality of the surface reservoirs of the Upper Jaguaribe, showing a correlation with the attributes of water quality, especially with pH. Total degradation of the surface waters of the Upper Jaguaribe Basin due to land use in the watersheds is just a matter of time.